2008
DOI: 10.1002/cbf.1522
|View full text |Cite
|
Sign up to set email alerts
|

Pax9 mediated cell survival in oral squamous carcinoma cell enhanced by c‐myb

Abstract: Paired box gene 9 (Pax9) and c-myb are transcription factors that regulate the expression of the genes involved in mediating cell proliferation, resistance to apoptosis, and migration. However, the function of Pax9 in oral squamous cell carcinoma (OSCC) is virtually unknown. This study examined the anti-apoptotic roles of Pax9 and c-myb, and clarified interaction between the two genes in KB cells. Inhibition of Pax9 caused the induction of apoptosis with enhanced cleavage of caspase-3 and PARP, accelerated Bax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…PAX9 is one of the nine members of "paired box” ( PAX )-containing transcription factor family and its inhibition has been shown to induce apoptosis with increased cleavage of caspase-3 and PARP , increased expression of BAX and decreased expression of BCL-2 in oral squamous cell carcinoma [53]. In the recent years, it has emerged as one of the biomarkers of cell proliferation in lung cancer [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAX9 is one of the nine members of "paired box” ( PAX )-containing transcription factor family and its inhibition has been shown to induce apoptosis with increased cleavage of caspase-3 and PARP , increased expression of BAX and decreased expression of BCL-2 in oral squamous cell carcinoma [53]. In the recent years, it has emerged as one of the biomarkers of cell proliferation in lung cancer [54].…”
Section: Discussionmentioning
confidence: 99%
“…This explanation is further supported by progressively increasing gene expression levels of PAX9 and CRY1 in coherence with advanced Rai stage and higher IPI scores. The mechanism(s) underlying such an influence of these two genes in CLL pathogenesis are not known but might involve apoptotic [53, 5557], or analogous pathways involved in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lee et al revealed that PAX9 inhibition causes the induction of apoptosis with enhanced cleavage of caspase-3 and poly ADP-ribose polymerase, increased expression levels of Bax and reduced expression levels of Bcl-2 in oral squamous cell carcinoma. In addition, cells transfected with PAX9 siRNA and cells infected with adenovirus-mediated expression of dominant-negative c-myb have been reported to display cell cycle arrest at the G 0 phase (30). The findings of the present study may support this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor expressed in the tooth mesenchyme during tooth morphogenesis, heterozygous mutations in PAX9 have been associated with non-syndromic tooth agenesis, predominantly in the molars (2528). In the last decade, the abnormal expression of the PAX9 gene, which is associated with the tumorigenesis, development, invasion and metastasis of many types of cancer, was observed in a variety of malignant human tumors (29,30). However, the expression level and prognostic value of PAX9 in malignant tumor cells remain inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Pax9 and c-myb expressions in KB cells seem to be essential for cell growth, and survival was enhanced by c-myb. Disruption of the function of c-myb and Pax9 induced G0 arrest [75].…”
Section: Salivary Gland Carcinomamentioning
confidence: 99%